Classification and Disintegration Characteristics of the Carboniferous Rocks in Guangxi, China. (19th November 2021) - Mo, Peng; Luo, Junhui; Mi, Decai; Chang, Zhenchao; Huang, Haifeng; Zhang, Tao; Sun, Guanhua; Li, Yan; Zeng, Ling; Wang, Shihai
Abstract : To investigate the disintegration characteristics of the carbonaceous rocks in Guangxi Province, the typical carbonaceous rocks in the section exposed by the Hechi-Baise Expressway were investigated in this study. First, based on their mineral compositions and contents, the carbonaceous rocks were divided into four types: carbonate chert, carbonaceous argillaceous limestone, carbonaceous illite clay mudstone, and carbonaceous illite clay shale. Then, through indoor wet-dry cyclic disintegration test, the disintegration characteristics of the four types of rocks were studied. The test results showed the following: (1) the disintegration residues of the carbonate chert and the carbonaceous argillaceous limestone decrease linearly as the number of wetting-drying cycles increases. (2) The disintegration index of the carbonaceous illite clay mudstone and the carbonaceous illite clay shale decreases exponentially as the number of wetting-drying cycles increases. (3) As the number of wetting-drying cycles increases, the disintegration index curves of the carbonaceous illite clay mudstone and the carbonaceous illite clay shale samples gradually become stable until the disintegration of the samples is completed. (4) The disintegration of carbonaceous rocks is mainly affected by the clay content, followed by the structural form, but it cannot be ignored.